TINJAUAN HUKUM ISLAM TERHADAP KHITAN BAGI PEREMPUAN (STUDI KOMPARASI ANTARA ULAMA KLASIK DAN ULAMA KONTEMPORER) - Faiz Izuddin Masykur; Fadhliah Mubakkirah (Program Studi Perbandingan Mazhab, Fakultas Syariah, Universitas Islam Negeri (UIN) Datokarama Palu, 2022)
Circumcision is cutting or removing part of the genitals, especially circumcision for women who still have issues that are disputed among classical and contemporary scholars. In Indonesia, there are also differences of opinion regarding circumcision between MUI Fatwa and PERMENKES. Therefore, a scientific work was made which discussed female circumcision in the framework of an Islamic legal review regarding legal comparisons between the views of classical and contemporary Islamic scholars. The main problem in this research is how the review of Islamic law regarding female circumcision between the views of classical and contemporary Islamic scholars. This study uses the library research method with a qualitative approach, using library research funds by exploring various literatures, including books, Al-Qur'an, hadith, journals, and websites that are continuous with the research theme. The results of this thesis research conclude that circumcision for women in the view of Classical and Contemporary scholars that circumcision has been prescribed by religion, but among scholars there is still a debate about female circumcision because in the Qur'an and hadith there is no clear explanation regarding circumcision women but only follow the millah of Prophet Ibrahim AS.